Storyways: Visualising Saintly Impact in a North Atlantic Maritime Landscape - Gibbon Sarah Jane; Moore James (Open Archaeology, 2019)
This paper presents a new methodological approach and theorising framework which visualises intangible landscapes. The Cult of Saint Magnus of Orkney (martyred c.AD1117 and canonised c.1135) is presented as a case study to demonstrate how spatial and temporal veneration can be explored in the landscape. The transferability of this methodology extends to any multi-source study where memories link to landscape features (past or present). St Magnus dedications, altars and church furnishings in Scandinavia and Britain demonstrate his international recognition, but aside from three Magnus dedicated churches, little is known of his veneration within Orkney. By using GIS to map archaeological, onomastic, folkloric, historic and hagiographic evidence of veneration we have visualised the impact of the Cult of Magnus since martyrdom to recent times for the first time. Furthermore, by visually differentiating between sources, we’ve distinguished the variability and variety of evidence, thus identifying concentrated pockets of veneration through time. Additionally, by linking evidence locations, we have identified ‘remembered’ routeways – storyways. In doing so, we have mapped the impact of Magnus as a saint, his value to particular communities and his continuing influence.